Family disintegration and juvenile delinquency Afield study conducted at the juvenile centers - Constantine and Ain Melilla - IDIOU, Leila (Journal of Human Sciences, 2020)
This study examines the current issue of family breakdown and its impact on deviant behaviors, in order to shed light on various aspects of the deviant personality of the offender (divorce, prolonged absence of one or both parents; bad conjugal relations, emotional deficiencies of the event within the family) and lead by to commit a deviant act.And given the nature of the subject, the type of study will necessarily be a descriptive study in which they will rely on the method of social inquiry, applying a questionnaire composed of 14 questions to a study population estimated at (69) juveniles, represented by juveniles in the juvenile centers of the cities of Constantine and Ain Melilla, in order to know the extent of the effect of this type of family on the behavior of their children, and how this pushes them towards delinquency and delinquent behavior.